Tablet containing a high amount of acotiamide or a salt thereof
Patent Information
- Application Number
- CN202580024050.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0039]本发明的含有阿考替胺或其盐的片剂是如下片剂:尽管在素片中含有65质量%以上且91质量%以下的高浓度的阿考替胺或其盐,但除了阿考替胺或其盐的良好的溶出性以外,即便在高湿度条件下保存后溶出性也不会降低,且片剂硬度也得到维持。因此,作为可谋求每一片的总重量降低,并且1次给予量增加时的服用性也优异的片剂。
Smart Images

Figure CN123022418A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a tablet containing a high amount of acotiamide or its salt. Background Technology
[0002] Acotiamide's chemical name is N-[2-[Bis(1-methylethyl)amino]ethyl]-2-[(2-hydroxy-4,5-dimethoxybenzoyl)amino]thiazole-4-carboxamide, with the molecular formula C 21 H 30 N4O5S. Acotiamide is known to improve gastrointestinal motility disorders by significantly promoting gastrointestinal motility (Patent Document 1), and its hydrochloride hydrate is commercially available as a treatment for functional dyspepsia.
[0003] Acofide (registered trademark) tablets 100mg containing acotiamide hydrochloride hydrate are tablets containing, in addition to acotiamide hydrochloride hydrate 100mg, lactose hydrate, crystalline cellulose, low-substituted hydroxypropyl cellulose, hydroxypropyl cellulose, light anhydrous silicate, magnesium stearate, hydroxypropyl methylcellulose, titanium dioxide, and carnauba wax, totaling 257mg in weight. In the treatment of the above-mentioned functional dyspepsia, the dosage is 100mg three times a day, taken before meals (Non-Patent Literature 1).
[0004] As a technique for miniaturizing tablets containing acotiamine or its salts, the following technique is reported: adding a water-insoluble first filler such as calcium sulfate to acotiamine hydrochloride hydrate, performing wet granulation, drying, adding a second filler such as α-starch and a disintegrant such as cross-linked carboxymethyl cellulose or low-substituted hydroxypropyl cellulose to the obtained granules, and compressing the granules to produce tablets containing a high amount of acotiamine hydrochloride (Patent Document 2).
[0005] Generally, tablets with high levels of active pharmaceutical ingredients are more difficult to form due to the limited amount of additives that can be incorporated into the formulation, making them prone to compression problems such as sticking or capping. As a countermeasure to improve compression problems in formulations containing high amounts of taurine, the following technology has been reported: coating the surface of micronized taurine powder with a water-soluble polymer and then compressing it (Patent Document 3).
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: International Publication No. 1996 / 36619
[0009] Patent Document 2: Chinese Application Publication No. 105769784
[0010] Patent Document 3: Japanese Patent Application Publication No. 11-060476
[0011] Non-patent literature
[0012] Non-patent literature 1: Acofide 100mg tablets summary instructions (interview form)
[0013] Non-patent literature 2: Res. Rep. Urol. 2015; 7: 81-83
[0014] Non-patent literature 3: Res. Rep. Urol. 2017; 9: 141-143
[0015] Non-patent literature 4: Int. J. Urol. 2019; 26(8): 848-849
[0016] Non-patent literature 5: Journal of the Japanese Society for Voiding Function. 2022; 33(1): 224 Summary of the Invention
[0017] Although the tablets containing acotilam or its salts described in Patent Document 2 have a reduced total weight and achieved miniaturization, the miniaturization of the tablets results in a higher content of active ingredients in each tablet, leading to problems such as reduced storage stability of the tablets.
[0018] Therefore, the objective of this invention is to provide a tablet containing acotiamine or its salt at a high concentration, which not only has good dissolution properties but also good storage stability and can be continuously compressed.
[0019] Therefore, the inventors conducted various studies to solve the above-mentioned problems, and found that by obtaining granules containing (A) acotiamide or its salt, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate, and then compressing them, tablets containing a high concentration of component (A) acotiamide or its salt in the unprocessed tablets (65% by mass and 91% by mass) can be obtained. These tablets, in addition to having good solubility, do not experience a decrease in solubility even after storage under high humidity conditions, and also maintain tablet hardness, thus completing the present invention. Furthermore, it was found that by adjusting the moisture content of the granules and tablets to an appropriate range, the uniformity of the distribution of the active ingredient in the obtained tablets is increased, the tablets have good solubility, and the decrease in hardness after storage under high humidity conditions is suppressed.
[0020] That is, the present invention provides the following [1] to
[18] .
[0021] [1] A tablet characterized in that it contains a granule comprising (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate, wherein the tablet contains more than 65% by mass and less than 91% by mass of component (A).
[0022] [2] The tablet as described in [1], wherein the granules are wet granules.
[0023] [3] The tablets as described in [1] or [2], wherein the content of component (B) in the unpasteurized tablets is more than 2% by mass and less than 10% by mass.
[0024] [4] The tablet as described in any one of [1] to [3], wherein the content of component (C) in the uncoated tablet is 5% by mass or more and 20% by mass or less.
[0025] [5] The tablet as described in any one of [1] to [4], wherein the total content of component (B) and component (C) in the uncoated tablet is 8% by mass or more.
[0026] [6] The tablet as described in any one of [1] to [5], wherein the content of component (B) in the uncoated tablet is 2% by mass or more and 8% by mass or less.
[0027] [7] The tablet as described in any one of [1] to [6], wherein the content of component (C) in the uncoated tablet is 5% by mass or more and 15% by mass or less.
[0028] [8] The tablet as described in any one of [1] to [7], wherein the total content of component (B) and component (C) in the uncoated tablet is 8% by mass or more and 25% by mass or less.
[0029] [9] The tablet as described in any one of [1] to [8], wherein the content of component (B) in the uncoated tablet is 3% by mass or more and 8% by mass or less.
[0030]
[10] The tablet as described in any one of [1] to [9], wherein the total content of component (B) and component (C) in the uncoated tablet is 8% by mass or more and 22% by mass or less.
[0031]
[11] A method for manufacturing a tablet comprising a step of compressing a wet granule containing (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate, wherein the tablet contains 65% by mass and 91% by mass of component (A) in the uncoated tablet.
[0032]
[12] A tablet comprising a wet granulated dry powder having a moisture content of 4.0% or more and 11.0% or less, wherein the granulated powder comprises (D) a pharmacologically active ingredient, (B) α-substituted starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate.
[0033]
[13] The tablets as described in
[12] , wherein the moisture content of the wet granulated dried powder is 4.0% or more and 9.0% or less.
[0034]
[14] The tablets as described in
[12] or
[13] , wherein the moisture content of the tablets is 4.0% or more and 13.0% or less.
[0035]
[15] Tablets such as
[12] or
[13] , wherein the moisture content of the tablets is more than 4.0% and less than 11.0%.
[0036]
[16] The tablet as described in any one of
[12] to
[15] , wherein (D) the active ingredient is acotilide or a salt thereof.
[0037]
[17] The tablet as described in any one of
[12] to
[16] , wherein the water retention ratio of component (A) and component (B) in the tablet is 0.07 or more and 2.4 or less.
[0038]
[18] The tablet as described in any one of
[12] to
[17] , wherein the water content ratio of component (A) and component (B) in the tablet is 0.15 or more and 2.0 or less.
[0039] The tablets containing acotiamide or its salts of the present invention are tablets that, despite containing a high concentration of acotiamide or its salts of 65% to 91% by mass in the uncoated tablet, exhibit good solubility of acotiamide or its salts of 65% to 91% by mass, and their solubility does not decrease even after storage under high humidity conditions, while also maintaining tablet hardness. Therefore, they are tablets with excellent palatability when the total weight of each tablet can be reduced and the single dose increased.
[0040] Furthermore, by adjusting the moisture content of the granules and tablets to an appropriate range, the uniformity of the distribution of the active pharmaceutical ingredient in the resulting tablets is improved, the tablets exhibit good dissolution properties, and the decrease in hardness after storage under high humidity conditions is suppressed. It should be noted that although the tablets of the present invention have a high drug content, they do not experience tableting obstacles such as lamination or cracking during tablet compression molding, and remain stable even in high-speed continuous tableting processes, thereby improving industrial production efficiency. Attached Figure Description
[0041] Figure 1This is a graph showing the relationship between the composition ratio of sulfur (acotelamine hydrochloride) and color.
[0042] Figure 2 This is a graph showing the uniformity of the distribution of acotiamide hydrochloride in the tablets of Examples 2, 4, Comparative Example 2, and Comparative Example 8.
[0043] Figure 3 This is a graph showing the uniformity of the distribution of acotiamide hydrochloride in the tablets of Comparative Example 10 and Comparative Example 11. Detailed Implementation
[0044] The tablets of the present invention containing acotiamide or its salts are high-concentration tablets in which the content of acotiamide or its salts in the unprocessed tablets is 65% by mass or more and 91% by mass or less.
[0045] One aspect of the present invention is a tablet characterized by containing a granulator comprising (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate, wherein the tablet contains more than 65% by mass and less than 91% by mass of component (A).
[0046] Acotiamide's chemical name is N-[2-[bis(1-methylethyl)amino]ethyl]-2-[(2-hydroxy-4,5-dimethoxybenzoyl)amino]thiazole-4-carboxamide, and its molecular formula is C2. 21 H 30 N4O5S. Acotiamide is known to improve gastrointestinal motility disorders by significantly promoting gastrointestinal motility (Patent Document 1), and its hydrochloride hydrate is commercially available as a treatment for functional dyspepsia. More specifically, the efficacy and effects of acotiamide-containing functional dyspepsia treatments are postprandial bloating, upper abdominal bloating, and early satiety in functional dyspepsia. Regarding its usage and dosage, for adults, the dosage is 100 mg of acotiamide hydrochloride hydrate, orally three times a day before meals.
[0047] Reports indicate that acotiamide or its salts are effective for voiding disorders in rats with a hypoactive bladder model and in pilot studies in patients with hypoactive bladders, in combination with α1-receptor blockers (Non-Patent Literature 2-5). Furthermore, regarding acotiamide or its salts, studies were conducted on detrusor contraction pressure, urine flow velocity, and urethral pressure at doses far exceeding those shown to improve gastrointestinal motility. The results showed that, unlike existing cholinergic agonists, at doses higher than those used to treat functional dyspepsia, it increased bladder contraction pressure and maximum contraction pressure during voiding without affecting urethral pressure, thus proving useful as a voiding disorder improver. When using acotiamide or its salts as a voiding disorder improver, it is preferable to administer acotiamide or its salts orally to adults at a dose of 200-300 mg once, 600-900 mg daily (Japanese Patent Application 2023-040926).
[0048] Salts of acotiamine can be acid addition salts, specifically, acid addition salts of inorganic acids such as hydrochloride, sulfate, nitrate, phosphate, hydrobromide, and hydroiodide; or acid addition salts of organic acids such as acetate, oxalate, malonate, succinate, maleate, fumarate, lactate, malate, citrate, tartrate, methanesulfonate, and ethanesulfonate. Acotiamine hydrochloride is more preferred. Various solvates, such as hydrates of acotiamine or its salts, are also included. Acotiamine hydrochloride hydrate is particularly preferred. These acotiamines or their salts can be manufactured, for example, by the method described in Patent Document 1 above.
[0049] From the viewpoint of improving dosing ease of administration through tablet miniaturization and from the viewpoint of improving the dosing ease of administration of such high-dose tablets as those administered orally at a single dose of 200 mg to 300 mg or daily at a dose of 600 mg to 900 mg, acotiamide or its salt is preferably contained in the uncoated tablets of the present invention at a content of 65% by mass or more and 91% by mass or less, more preferably 65% by mass or more and 88% by mass or less, and even more preferably 65% by mass or more and 75% by mass or less. When using acotiamide or its salt as a urinary disorder improver, the single dose increases, therefore this content is particularly preferred.
[0050] The tablets of the present invention contain granules comprising (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate. That is, in the tablets of the present invention, from the viewpoint that in addition to good solubility, the solubility does not decrease even after storage under high humidity conditions, and the tablet hardness is maintained, it is preferable that the granules contain (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate.
[0051] (B) α-Created starch is obtained by heating starch from wheat, corn, potato, rice, cassava, etc. with water under normal or pressure conditions, thereby α-coating (gelatinizing) the starch granules, and then drying the resulting substance.
[0052] The (B) α-starch in this invention includes any of the “α-starch”, “partially α-starch”, and α-starch that can generally be added to pharmaceuticals and food, as contained in Pharmaceutical Additives Standard 2018.
[0053] Commercially available α-starch products include PCS PC-10 (Asahi Kasei Corporation) and SWELSTAR. TM WB-1 (Asahi Kasei Co., Ltd.), SWELSTAR TM PD-1 (Asahi Kasei Co., Ltd.), SWELSTAR TM MX-1 (Asahi Kasei Corporation), Corn Alpha W (Sanwa Starch Industry Co., Ltd.), Waxy Alpha Y (Sanwa Starch Industry Co., Ltd.), TapiocaAlpha NTP (Sanwa Starch Industry Co., Ltd.), Lycatab TM C(Roquette Frères)、Lycatab TM CLM (Roquette Frères), Lycatab TM CT (Roquette Frères), Lycatab TM PGS (Roquette Frères), Starch 1500 TM (Colorcon), Starch 1500 TM LM (Colorcon), Starch 1500 TM G (Colorcon), Prejel PA5 PH (DFE Pharma), Nutrofeli TM ST200 (DFE Pharma), Nutrofeli TM ST300 (DFE Pharma), etc.
[0054] From the viewpoint of dissolution and tablet stability, the content of α-starch in the unprocessed tablets is preferably 2% by mass or more and 10% by mass or less, more preferably 2% by mass or more and 8% by mass or less, and even more preferably 3% by mass or more and 8% by mass or less.
[0055] As for (B) α-starch, α-starch with a cold water soluble content of 1.0% or more is preferred. Here, cold water soluble content is defined as a value obtained by the following determination method.
[0056] <Determination Method of Cold Water Soluble Matter (%)>
[0057] Approximately 1g (W) of sample A0 Add 99g of purified water at 20±5℃ to the solution and stir for 2 hours to disperse it. Transfer 40mL of the resulting dispersion to a 50mL centrifuge tube and centrifuge (approximately 5000g, 15 minutes). Dry 20mL of the supernatant at 110℃ to a certain mass and calculate the dry mass W of the water-soluble substance. A (g). Additionally, approximately 1g (W) of the sample was taken. B0 The sample was dried at 110℃ to a certain mass, and the dried mass W of the sample was calculated. B (g) The value calculated using these values and the following formula shall be taken as the percentage of cold water solubles.
[0058] Cold water soluble matter (%) = (W A / W A0 ×100 / 20) / (W) B / W B0 )×100
[0059] Component (C) is a disintegrant. Specifically, it is preferably one or two selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate.
[0060] From the viewpoint of dissolution, the disintegrant used in this invention preferably has a water retention capacity of 500% or more. Here, water retention capacity is defined as a value obtained by the measurement method described below.
[0061] <Methods for determining water retention>
[0062] Add 15 mL of purified water at 20±5℃ to approximately 1 g (W0) of the sample placed in a 50 mL centrifuge tube, disperse the sample, and shake at 200 rpm for 10 minutes. Add another 15 mL of purified water at 20±5℃, let stand for 20 minutes, and then centrifuge (approximately 2000 G, 10 minutes). The water retention (%) is calculated using the following formula based on the mass W (g) of the residue after removing the supernatant and the initial sample mass W0 (g).
[0063] Water retention capacity (%) = (W - W0) / W × 100
[0064] Low-substitution hydroxypropyl cellulose is a cellulose derivative in which a small amount of hydroxypropoxy groups are introduced into the glucose ring of cellulose. The molar degree of substitution of hydroxypropoxy groups in typical hydroxypropyl cellulose is 3, and preferably 0.2 to 0.4. Here, the molar degree of substitution is the average number of hydroxyl groups substituted with hydroxypropoxy groups per glucose molecule.
[0065] As a commercially available product of low-substituted hydroxypropyl cellulose, L-HPC can be cited as an example. TM (Shin-Etsu Chemical Industry Co., Ltd.). Several varieties are commercially available, including L-HPC. TM Examples of such varieties include LH-11, LH-21, LH-22, LH-B1, LH-31, LH-32, NBD-020, NBD-021, and NBD-022.
[0066] Sodium starch glycolate is the sodium salt of carboxymethyl ether of starch or its crosslinked derivatives. It has neutralization types A and B, and when quantified separately, the substance obtained by drying the insoluble matter of an ethanol (99.5%) / water mixture (8:2) contains 2.8%–4.2% and 2.0%–3.4% sodium (Na: 22.99%), respectively.
[0067] GLYCOLYS is a commercially available product that produces sodium starch glycolate. TM (Roquette Frères), Primojel TM (DFE Pharma), EXPLOTAB TM (JRS Pharma), EXPLOTAB TM CLV (JRS Pharma), EXPLOTAB TM PCF (JRS Pharma), EXPLOTAB TM LowpH (JRS Pharma), etc.
[0068] From the viewpoint of dissolution and tablet stability, the content of disintegrants selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate is preferably 5% by mass or more and 20% by mass or less in unprocessed tablets, more preferably 5% by mass or more and 15% by mass or less.
[0069] From the viewpoint of dissolution and tablet stability, the amount of α-starch (B) relative to 100 parts by mass of component (A) (acotiamine or its salt) is preferably 2 parts by mass or more and 15 parts by mass or less, more preferably 2 parts by mass or more and 11 parts by mass or less, and even more preferably 3 parts by mass or more and 11 parts by mass or less.
[0070] From the viewpoint of dissolution and tablet stability, the disintegrant (C) selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate preferably contains 5 or more but less than 30 parts by weight relative to 100 parts by weight of component (A) (acotiamide or its salt), more preferably 5 or more but less than 20 parts by weight.
[0071] From the viewpoint of dissolution and tablet stability, the total content of component (B) α-substituted starch and (C) disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate in the unprocessed tablet is preferably 8% by mass or more, more preferably 8% by mass or more and 25% by mass or less, and even more preferably 8% by mass or more and 22% by mass or less.
[0072] From the viewpoint of dissolution and tablet stability, the mass ratio (C / B) of the disintegrant (C) selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate to (B) α-substituted starch is preferably 1 or more and 6 or less, more preferably 1 or more and 3 or less.
[0073] From the viewpoint of dissolution and tablet stability, the average particle size D50 of the granules containing the above-mentioned components (A), (B) and (C) is preferably 90 μm or more and 700 μm or less, and more preferably 120 μm or more and 500 μm or less.
[0074] In addition to components (A), (B), and (C) mentioned above, the granules may also contain excipients commonly used in tablet manufacturing. Examples of such excipients include crystalline cellulose, lactose, powdered cellulose, mannitol, white sugar, corn starch, and potato starch. Among these excipients, crystalline cellulose, lactose, and powdered cellulose are more preferred.
[0075] From the viewpoint of dissolution and tablet stability, the content of these excipients in the granules is preferably 25% by mass or less, more preferably 11% by mass or less, and even more preferably 8% by mass or less, from the viewpoint of tablet miniaturization.
[0076] Another aspect of the present invention is a method for manufacturing a tablet comprising a step of compressing a granule containing (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate, wherein the tablet contains 65% by mass and 91% by mass of component (A) in the unprocessed tablet.
[0077] From the viewpoints of dissolution, tablet stability, and manufacturability, wet granulation is preferred.
[0078] The granules described above can be mixed with the above components (A), (B), (C) and excipients as needed, and manufactured by conventional granulation methods, preferably wet granulation methods.
[0079] Examples of wet granulation methods include stirred granulation, fluidized bed granulation, and rolling fluidized bed granulation.
[0080] Specifically, the above-mentioned components (A), (B), and (C) are mixed with the desired excipient, water or a water / ethanol mixture is added, and the mixture is granulated using the above-mentioned granulation apparatus, followed by drying and granulation. Alternatively, the above-mentioned components (A) and (C) are mixed with the desired excipient, water or a water / ethanol mixture containing (B) is added, and the mixture is granulated using the above-mentioned granulation apparatus, followed by drying and granulation. It should be noted that regarding the amount of liquid added during granulation, in the case of stirred granulation, it is preferably 25-60% by mass relative to the feed rate for granulation; in the case of fluidized bed granulation and rolling fluidized bed granulation, it is preferably 25-100% by mass relative to the feed rate for granulation.
[0081] By adding lubricants, fluidizing agents, excipients, etc., as needed to the obtained granules and then compressing them, the tablets of the present invention can be obtained.
[0082] The above-mentioned excipients can be used as excipients. Magnesium stearate, sodium stearate fumarate, sodium lauryl sulfate, carnauba wax, polyethylene glycol, etc., can be used as lubricants. Magnesium stearate and sodium stearate fumarate are preferred among these.
[0083] As a fluidizing agent, light anhydrous silica, heavy anhydrous silica, magnesium aluminum metasilicate, synthetic aluminum silicate, talc, etc. can be used. Among them, light anhydrous silica is preferred.
[0084] Regarding the amount of these lubricants, fluidizing agents, excipients, etc. added, since the raw film contains 65% by mass or more and 91% by mass or less of component (A), it is preferable to add a small amount.
[0085] In addition, the tablets of the present invention can be plain tablets obtained in this manner, or the plain tablets can be coated with a film.
[0086] Furthermore, the inventors have discovered that by adjusting the moisture content of the granules and tablets to 4.0% or more and 11.0% or less, the uniformity of the distribution of the active ingredients in the obtained tablets is increased, the dissolution of the obtained tablets is good, and the decrease in hardness after storage under high humidity conditions is suppressed.
[0087] That is, another aspect of the present invention is a tablet containing a wet-granulated dry powder having a moisture content of 4.0% or more and 11.0% or less, wherein the wet-granulated dry powder comprises (D) a pharmaceutically active ingredient, (B) α-substituted starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate.
[0088] Here, as the pharmacologically active ingredient (D), (A) acotiamide or its salt is preferred, but not limited thereto.
[0089] From the viewpoint of dissolution and tablet stability, the moisture content of the aforementioned wet-granulated dried powder is preferably 4.0% or more and 11.0% or less, more preferably 4.0% or more and 9.0% or less. Methods for determining the moisture content include the loss on drying method, Karl Fischer titration, and near-infrared analysis.
[0090] From the viewpoint of dissolution and tablet stability, the moisture content of the tablets obtained according to the present invention is preferably 4.0% or more and 13.0% or less, more preferably 4.0% or more and 11.0% or less. Here, as a method for determining the moisture content, the drying loss method, Karl Fischer titration method, and near-infrared analysis method can be cited.
[0091] Furthermore, from the viewpoint of dissolution and tablet stability, the water retention ratio of component (A) and component (B) in the tablet is preferably 0.07 or more and 2.4 or less, more preferably 0.15 or more and 2.0 or less.
[0092] From the viewpoint of dissolution and tablet stability, the distribution of the pharmacologically active ingredient (D) in the tablets of the present invention is preferably such that ingredient (D) is not locally present, that is, ingredient (D), α-substituted starch (B), and disintegrant (C) selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate are uniformly distributed within the tablet. Methods for evaluating the distribution of ingredients within the tablet include elemental analysis of the tablet surface and / or tablet cross-section using energy dispersive X-ray spectrometry (EDS), Auger electron spectroscopy (AES), laser-induced breakdown spectroscopy (LIBS), X-ray photoelectron spectroscopy (XPS), or fluorescence X-ray analysis; and component mapping analysis of the tablet surface and / or tablet cross-section using time-of-flight secondary ion mass spectrometry (TOF-SIMS) or micro-Raman spectrophotometry.
[0093] The preferred examples, contents, and contents of components (B) and (C) in the tablets of this method are the same as those in the tablets described above.
[0094] Although the tablets of the present invention have a high content of acotiamide or its salt (A), the dissolution of component (A) is good, resulting in good storage stability. In particular, the dissolution does not decrease even when stored under high humidity conditions, and the tablet hardness is also maintained. Therefore, it is possible to further miniaturize tablets containing 100 mg of component (A), and miniaturization is possible even when the content of component (A) in a tablet increases, thereby improving the ease of use.
[0095] Example
[0096] Next, embodiments will be given to further illustrate the invention in detail, but the invention is not limited to these embodiments.
[0097] (Raw materials used)
[0098] In the embodiments of the present invention, acotiamide hydrochloride hydrate was obtained by pulverizing by Zhirui Pharmaceutical Co., Ltd. using a pulverizer, and the water retention (%) was 59%.
[0099] The (B) α-substituted starch used in the examples is shown in Table 1.
[0100] [Table 1]
[0101]
[0102] The low-substituted hydroxypropyl cellulose used in the examples is shown in Table 2.
[0103] [Table 2]
[0104]
[0105] The sodium starch glycolate used in the examples is shown in Table 3.
[0106] [Table 3]
[0107]
[0108] (Granulation device)
[0109] The table lists the stirred granulation device, fluidized bed granulation device, or rolling fluidized bed granulation device.
[0110] (Tableting conditions)
[0111] The tableting pressure described in the examples.
[0112] (Determination of moisture content)
[0113] The weight loss was determined using the drying loss test method described in the Japanese Pharmacopoeia, at 80°C for 20 minutes.
[0114] (Tablet hardness determination)
[0115] The hardness was measured using a PHARMA TEST PTB-502 hardness tester.
[0116] (Determination of dissolution rate)
[0117] Dissolution tests were conducted using the liquid-covering method (test solution: water or dissolution test solution 2, paddle speed: 50 rpm) as specified in the Japanese Pharmacopoeia, and the dissolution rate (%) was calculated 15 minutes after the start of the test.
[0118] (Storage conditions for tablets)
[0119] In a constant temperature and humidity test chamber set at 40℃ / 75%RH, the tablets were stored under open conditions for 1 or 2 weeks.
[0120] (Evaluation of the uniformity of acotiamide hydrochloride hydrate within the tablet)
[0121] Elemental analysis of the tablet surface was performed using laser-induced breakdown spectroscopy (LAS-PDS) with a microscope equipped with a laser elemental analysis head. The measurement area was the central portion (720 μm × 450 μm) of the top surface of the tablet, with 400 measurement points spaced 30 μm apart. Oxygen, carbon, hydrogen, sulfur, and silicon were selected as the detectable elements, and elemental analysis was performed to calculate their composition ratios. Based on the obtained measurement results, [the following is a continuation of the analysis]. Figure 1 The colors shown are mapped to the ratio of sulfur in the composition.
[0122] (evaluate)
[0123] Regarding the initial hardness of the tablets, a value above 120N is defined as... Set anything less than 120N to ×.
[0124] Regarding the dissolution rate of the active ingredient, a dissolution rate of 85% or higher at 15 minutes after the start of the dissolution test is defined as... Set less than 85% to ×.
[0125] Regarding the hardness reduction rate after storage, below 30% is defined as... Set ○ to 30% and less than 50%, and set × to more than 50%.
[0126] Regarding the dissolution rate after storage, 85% or more is set as... Set less than 85% to ×.
[0127] Regarding the uniformity of acotiamide hydrochloride hydrate within the tablets, the condition was defined as having fewer than 5 points out of 400 points where the sulfur composition ratio was above 60%. A score of 5 or more but less than 10 points with a sulfur content of 60% or more is marked as ○, and a score of 10 or more points with a sulfur content of 60% or more is marked as ×.
[0128] Example 1
[0129] Acotiamide hydrochloride hydrate (75.0% by mass), α-starch A (5.0% by mass), lactose hydrate (6.0% by mass), crystalline cellulose (2.0% by mass), and low-substituted hydroxypropyl cellulose A (10.0% by mass) were mixed, and water at 33.5% by mass relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and granulated using a granulator with a sieve diameter of 1.905 mm. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was then compressed to a diameter of 10.5 mm under a tableting pressure of 10.7 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0130] Example 2
[0131] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 57.4 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.1 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0132] Example 3
[0133] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at a ratio of 31.3 wt% relative to the granulation components was added. The mixture was then granulated and dried in a fluidized bed granulator, and sieved through an 850 μm sieve. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the resulting granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.2 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0134] Example 4
[0135] Acotiamide hydrochloride hydrate (75.4% by mass), crystalline cellulose (8.0% by mass), and low-substituted hydroxypropyl cellulose A (10.1% by mass) were mixed, and a binding solution obtained by dispersing α-starch B (5.0% by mass) in water at a ratio of 45.9% by mass relative to the granulation components was added. The mixture was then granulated and dried in a rolling fluidized bed granulator, and finally sieved through an 850 μm sieve. Magnesium stearate (1.5% by mass) was added to the resulting granules, and after mixing, the mixture was compressed to a diameter of 10.5 mm under tableting pressures of 11.0 kN and 15.0 kN to manufacture 398 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0136] Example 5
[0137] Acotiamide hydrochloride hydrate (66.7% by mass), α-starch A (5.0% by mass), lactose hydrate (4.3% by mass), crystalline cellulose (2.0% by mass), and low-substituted hydroxypropyl cellulose A (20.0% by mass) were mixed, and water was added at 49.0% by mass relative to the granulation components. The mixture was then stirred and granulated. The granules were then dried at 80°C and granulated using a granulator with a 1.905 mm sieve diameter. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the resulting granules, and the mixture was then compressed to a diameter of 11 mm under a tableting pressure of 10.9 kN to produce 450 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0138] Example 6
[0139] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (11.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (2.0 wt%) in water at 44.6 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0140] Example 7
[0141] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (2.0 wt%), powdered cellulose (3.5 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed. A binding solution obtained by dispersing α-starch B (7.5 wt%) in water at a concentration of 45.8 wt% relative to the granulation components was added. The mixture was granulated and dried in a rolling fluidized bed granulator, and then sieved through an 850 μm sieve. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the resulting granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 10.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0142] Example 8
[0143] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (3.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (10.0 wt%) in water at 44.6 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0144] Example 9
[0145] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch C (5.0 wt%) in water at 44.6 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0146] Example 10
[0147] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch D (5.0 wt%) in water at 44.6 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0148] Example 11
[0149] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose C (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 44.6 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm mesh. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.1 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0150] Example 12
[0151] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose D (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 44.6 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.1 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0152] Example 13
[0153] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose E (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 44.6 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0154] Example 14
[0155] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and sodium starch glycolate (10.0 wt%) with a water retention of 1625% were mixed. A binding solution was added to disperse α-starch B (5.0 wt%) in water at 57.4 wt% relative to the granulation components, and the mixture was stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.1 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0156] Example 15
[0157] Acotiamide hydrochloride hydrate (85.7% by mass), crystalline cellulose (4.1% by mass), and low-substituted hydroxypropyl cellulose A (5.1% by mass) were mixed, and a binding solution obtained by dispersing α-starch B (3.0% by mass) in water at 36.4% by mass relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to manufacture 350 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0158] Example 16
[0159] Acotiamide hydrochloride hydrate (90.9% by mass) and low-substituted hydroxypropyl cellulose A (5.2% by mass) were mixed, and a binding solution obtained by dispersing α-starch B (2.9% by mass) in water at 38.3% by mass relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm mesh. Magnesium stearate (1.0% by mass) was added to the resulting granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to produce 330 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0160] Example 17
[0161] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (13.0 wt%), and sodium starch glycolate B (5.0 wt%) were mixed, and granulation was carried out while stirring, by adding a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 44.6 wt% relative to the granulation components. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, mixed, and then compressed into tablets with a diameter of 10.5 mm under a tableting pressure of 15.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0162] Example 18
[0163] Acotiamide hydrochloride hydrate (66.7% by mass), crystalline cellulose (6.3% by mass), and sodium starch glycolate A (20.0% by mass) were mixed, and a binding solution obtained by dispersing α-starch B (5.0% by mass) in water at a ratio of 61.2% by mass relative to the granulation components was added while stirring and granulating. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 7.2 kN to manufacture 450 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0164] Example 19
[0165] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed. A binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 96.9 wt% relative to the granulation components was added. The mixture was then granulated and dried in a fluidized bed granulator, followed by granulation using a granulator with a 1.4 mm screen diameter. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the resulting granules, and the mixture was then compressed into tablets with a long diameter of 13.0 mm and a short diameter of 6.9 mm using a high-speed rotary tablet press at a compression pressure of 9.4 kN, producing 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0166] Example 20
[0167] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at a ratio of 45.9 wt% relative to the granulation components was added. The mixture was then granulated and dried in a rolling fluidized bed granulator, and finally sieved through an 850 μm sieve. The particle size D50 of the granules was 278.7 μm, and the moisture content at the drying endpoint was 6.91%. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed into tablets with a diameter of 10.5 mm under a tableting pressure of 9.6 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate. The tablets were sprayed with a coating solution consisting of hydroxypropyl methylcellulose, titanium dioxide, and purified water to form film-coated tablets. The initial hardness and dissolution rate of the tablets were 241.8 N and 88.2%, respectively. After storage for 6 months, the tablets showed a decrease in hardness and a dissolution rate of 88.7%, respectively.
[0168] Example 21
[0169] Acotiamide hydrochloride hydrate (66.7% by mass), crystalline cellulose (6.3% by mass), low-substituted hydroxypropyl cellulose A (15.0% by mass), and sodium starch glycolate A (5.0% by mass) were mixed, and a binding solution obtained by dispersing α-starch B (5.0% by mass) in water at a ratio of 51.0% by mass relative to the granulation components was added while stirring and granulating. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, mixed, and then compressed to a diameter of 10.5 mm under a tableting pressure of 6.6 kN to manufacture 450 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0170] Example 22
[0171] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (12.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and granulation was carried out while stirring, by adding a binding solution obtained by dispersing α-starch B (1.0 wt%) in water at 44.6 wt% relative to the granulation components. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the obtained granules, mixed, and then compressed to a diameter of 10.5 mm under a tableting pressure of 6.7 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0172] Example 23
[0173] Acotiamide hydrochloride hydrate (66.7% by mass), crystalline cellulose (6.3% by mass), low-substituted hydroxypropyl cellulose A (17.0% by mass), and α-starch E (8.0% by mass) were mixed and granulated by stirring while adding water at 34.0% by mass relative to the granulation components. The granules were then dried at 80°C and sieved through an 850 μm mesh. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 6.7 kN to manufacture 450 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0174] Example 24
[0175] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and low-substituted hydroxypropyl cellulose A (10.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 96.9 wt% relative to the granulation components was added, while the mixture was subjected to rolling fluidized bed granulation. The granules were then dried at 80°C and granulated using a granulator with a sieve diameter of 1.905 mm. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the resulting granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 10.9 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0176] Comparative Example 1
[0177] Acotiamide hydrochloride hydrate (75.0% by mass) and crystalline cellulose (23.0% by mass) were mixed, and water (28.7% by mass relative to the granulation components) was added, followed by stirring and granulation. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0178] Comparative Example 2
[0179] Acotiamide hydrochloride hydrate (75.0 wt%) and crystalline cellulose (18.0 wt%) were mixed, and a binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 28.7 wt% relative to the granulation components was added. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0180] Comparative Example 3
[0181] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and crospovidone (10.0 wt%) with a water retention of 670% were mixed. A binding solution obtained by dispersing α-starch B (5.0 wt%) in water at a concentration of 45.9 wt% relative to the granulation components was added. The mixture was then granulated and dried in a rolling fluidized bed granulator, and finally sieved through an 850 μm sieve. Light anhydrous silicate (1.0 wt%) and magnesium stearate (1.0 wt%) were added to the resulting granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 10.6 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0182] Comparative Example 4
[0183] Acotiamide hydrochloride hydrate (75.0 wt%), crystalline cellulose (8.0 wt%), and carboxymethyl cellulose (10.0 wt%) with a water retention of 215% were mixed. A binding solution obtained by dispersing α-starch B (5.0 wt%) in water at 31.9 wt% relative to the granulation components was added, and the mixture was stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0184] Comparative Example 5
[0185] Acotiamide hydrochloride hydrate (75.0% by mass), crystalline cellulose (13.0% by mass), and low-substituted hydroxypropyl cellulose A (10.0% by mass) were mixed, and water was added at 47.8% by mass relative to the granulation components. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5% by mass) and magnesium stearate (1.5% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0186] Comparative Example 6
[0187] Acotiamide hydrochloride hydrate (66.7% by mass), hydroxypropyl methylcellulose (5.0% by mass), lactose hydrate (4.3% by mass), crystalline cellulose (2.0% by mass), and low-substituted hydroxypropyl cellulose A (20.0% by mass) were mixed, and water was added at 34.0% by mass relative to the granulation components. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm mesh. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was then compressed to a diameter of 11.5 mm under a tableting pressure of 11.8 kN to manufacture 450 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0188] Comparative Example 7
[0189] Acotiamide hydrochloride hydrate (66.7% by mass), hydroxypropyl cellulose (5.0% by mass), lactose hydrate (4.3% by mass), crystalline cellulose (2.0% by mass), and low-substituted hydroxypropyl cellulose A (20.0% by mass) were mixed, and water was added at 34.0% by mass relative to the granulation components. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm mesh. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was then compressed to a diameter of 11.5 mm under a tableting pressure of 10.6 kN to manufacture 450 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0190] Comparative Example 8
[0191] Acotiamide hydrochloride hydrate (75.0% by mass), crystalline cellulose (13.0% by mass), and low-substituted hydroxypropyl cellulose A (10.0% by mass) were mixed, and water was added at 47.8% by mass relative to the granulation components. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (1.0% by mass) and magnesium stearate (1.0% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0192] Comparative Example 9
[0193] A bound solution containing α-starch B (10.0% by mass) dispersed in 25% ethanol at a granulation concentration of 29.4% by mass relative to the granulation components was added to acotiamide hydrochloride hydrate (75.0% by mass), and the mixture was stirred and granulated. The granules were then dried at 50°C and sieved through an 850 μm sieve. Crystalline cellulose (8.5% by mass), crospovidone (5.0% by mass) with a water retention of 312%, and magnesium stearate (1.5% by mass) were added to the obtained granules, mixed, and then compressed to a diameter of 10.5 mm under a tableting pressure of 14.8 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0194] Comparative Example 10
[0195] A bound solution containing α-starch B (4.3% by mass) dispersed in water at a concentration of 20.3% by mass relative to the granulation components was added to acotiamide hydrochloride hydrate (84.9% by mass), and the mixture was stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Low-substituted hydroxypropyl cellulose A (8.7% by mass) and magnesium stearate (2.0% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to produce 345 mg tablets containing 293 mg of acotiamide hydrochloride hydrate.
[0196] Comparative Example 11
[0197] Acotiamide hydrochloride hydrate (75.6% by mass) and hydroxypropyl cellulose (2.7% by mass) were mixed, and water (6.8% by mass relative to the granulation components) was added. The mixture was then stirred and granulated. The granules were dried at 80°C and sieved through an 850 μm sieve. α-starch D (8.0% by mass), crystalline cellulose (9.3% by mass), corn starch (2.7% by mass), light anhydrous silica (1.3% by mass), and magnesium stearate (0.5% by mass) were added to the obtained granules. After mixing, the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 377 mg tablets containing 285 mg of acotiamide hydrochloride hydrate.
[0198] Comparative Example 12
[0199] A mixture of acotiamide hydrochloride hydrate (76.4% by mass), α-starch B (13.4% by mass), methylcellulose (2.3% by mass), low-substituted hydroxypropyl cellulose B (6.9% by mass), and magnesium stearate (0.9% by mass) was mixed to attempt to manufacture 432 mg tablets with a diameter of 10.5 mm containing 330 mg of acotiamide hydrochloride hydrate. However, the tableting powder had poor flowability and could not be manufactured.
[0200] Comparative Example 13
[0201] Acotiamide hydrochloride hydrate (58.0% by mass) and calcium sulfate (18.0% by mass) were mixed, and 40% ethanol (20.6% by mass relative to the granulation components) was added. The mixture was then stirred and granulated. The granules were dried at 45°C and sieved through an 850 μm sieve. α-starch B (15.0% by mass), low-substituted hydroxypropyl cellulose A (8.8% by mass), and magnesium stearate (0.2% by mass) were added to the obtained granules. After mixing, the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to produce tablets containing 200 mg of acotiamide hydrochloride hydrate, totaling 344.7 mg.
[0202] Comparative Example 14
[0203] Acotiamide hydrochloride hydrate (75.0% by mass) and calcium sulfate (10.0% by mass) were mixed, and 40% ethanol (19.6% by mass relative to the granulation components) was added. The mixture was then stirred and granulated. The granules were dried at 45°C and sieved through an 850 μm sieve. Alpha-substituted starch B (5.7% by mass), low-substituted hydroxypropyl cellulose A (8.8% by mass), and magnesium stearate (0.5% by mass) were added to the obtained granules. After mixing, the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 15.0 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0204] Comparative Example 15
[0205] Acotiamide hydrochloride hydrate (75.6% by mass) and hydroxypropyl cellulose (2.7% by mass) were mixed, and water (16.9% by mass relative to the granulation components) was added. The mixture was then stirred and granulated. The granules were dried at 80°C and sieved through an 850 μm sieve. α-starch D (8.0% by mass), crystalline cellulose (9.3% by mass), corn starch (2.7% by mass), light anhydrous silicate (1.3% by mass), and magnesium stearate (0.5% by mass) were added to the obtained granules. After mixing, the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 11.0 kN to manufacture 400 mg tablets containing 302 mg of acotiamide hydrochloride hydrate.
[0206] Comparative Example 16
[0207] A bound solution containing α-starch B (4.3% by mass) dispersed in water at a concentration of 28.4% by mass relative to the granulation components was added to acotiamide hydrochloride hydrate (84.9% by mass), and the mixture was stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Low-substituted hydroxypropyl cellulose A (8.7% by mass) and magnesium stearate (2.0% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 14.6 kN to produce 400 mg tablets containing 340 mg of acotiamide hydrochloride hydrate.
[0208] Comparative Example 17
[0209] Acotiamide hydrochloride hydrate (75.0% by mass), crystalline cellulose (13.0% by mass), and sodium starch glycolate A (10.0% by mass) were mixed, and water was added at 44.6% by mass relative to the granulation components. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5% by mass) and magnesium stearate (1.5% by mass) were added to the obtained granules, and the mixture was compressed to a diameter of 10.5 mm under a tableting pressure of 10.4 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0210] Comparative Example 18
[0211] Acotiamide hydrochloride hydrate (75.0 wt%), hydroxypropyl methylcellulose (5.0 wt%), crystalline cellulose (8.0 wt%), and sodium starch glycolate A (10.0 wt%) were mixed, and water was added at 44.6 wt% relative to the granulation components. The mixture was then stirred and granulated. The granules were then dried at 80°C and sieved through an 850 μm sieve. Light anhydrous silicate (0.5 wt%) and magnesium stearate (1.5 wt%) were added to the obtained granules, and the mixture was then compressed to a diameter of 10.5 mm under a tableting pressure of 14.6 kN to manufacture 400 mg tablets containing 300 mg of acotiamide hydrochloride hydrate.
[0212] The results of the obtained granules are shown in Tables 4 to 7.
[0213] The results of tablets stored for 2 weeks under open conditions in a constant temperature and humidity test chamber set at 40℃ / 75%RH are shown in Tables 4-5.
[0214] In addition, the evaluation results of tablets stored under the same conditions for 1 week are shown in Tables 6 and 7.
[0215] The ratio of the water retention of acotitam hydrochloride hydrate to α-starch in the tablets obtained in Examples 1-24 is shown in Table 8.
[0216] Granulation was carried out at a scale of 130 kg, and tableting was performed using a high-speed rotary tablet press at a rotation speed of 30 rpm, 40 rpm, and 50 rpm. The appearance inspection results, tableting pressure deviation (%), and mass variation coefficient (%) of the resulting tablets are shown in Table 9.
[0217] [Table 4]
[0218]
[0219] [Table 5]
[0220]
[0221] [Table 6]
[0222]
[0223] [Table 7]
[0224]
[0225] The water retention ratio is calculated as (water retention of α-starch / 100 × mass of α-starch in the formula (%)) / (water retention of acotiamine or its salt / 100 × mass of acotiamine or its salt in the formula (%)).
[0226] [Table 8]
[0227]
[0228] [Table 9]
[0229]
[0230] Based on the results of Comparative Example 12, from a manufacturing point of view, it is difficult to compress tablets without a granulation process when the tablets contain a high content of acotilam hydrochloride hydrate.
[0231] Based on the results of Comparative Example 1 and Comparative Example 2, it can be seen that when the granules do not contain (C) low-substituted hydroxypropyl cellulose or sodium starch glycolate, there is a problem of poor dissolution.
[0232] According to the results of Comparative Example 5, when the granules do not contain component (B) α-starch, there is a problem of reduced hardness after storage under high humidity conditions.
[0233] According to the results of Comparative Examples 9 and 10, when a disintegrant is added to granules containing component (A) acotiamine hydrochloride and component (B), there is a problem of reduced hardness after storage under high humidity conditions.
[0234] In contrast, the results of Examples 1 to 16 show that when granules containing components (A), (B), and (C) are present, the dissolution is good and the hardness reduction after storage under high humidity conditions is suppressed to a low extent, thus achieving the effects of the present invention.
[0235] Based on the results of Examples 1, 6, 7, 13 and 14, it was confirmed that, from the viewpoint of tablet dissolution, the binder added to the granules is suitable to be component (B) α-starch.
[0236] Based on the results of Examples 2, 9 and 10, it was confirmed that even components (B) with different values of cold water soluble content exerted the effects of the present invention.
[0237] Based on the results of Examples 2, 14, 3, and 4, it was confirmed that, from the viewpoint of dissolution and tablet stability, the disintegrant added to the granules is suitable as component (C) low-substituted hydroxypropyl cellulose or sodium starch glycolate.
[0238] Based on the results of Examples 2, 11 to 14, it was confirmed that the effect of the present invention is achieved if the water retention capacity of the above-mentioned disintegrant is 500% or more.
[0239] Based on the results of Example 16, it was confirmed that the effects of the present invention could be obtained even when the content of acotiamide hydrochloride hydrate was 90.9%.
[0240] Based on the results of Examples 2, 6, 7, 8 and 15, it was confirmed that if the content of α-starch in component (B) decreases or increases, there is a tendency for the hardness to decrease and increase after storage under high humidity conditions, and there is a range of component (B) content that is optimal for the stability of tablets.
[0241] Based on the results of Examples 2, 5, 14 and 15, it was confirmed that if the content of low-substituted hydroxypropyl cellulose or sodium starch glycolate of component (C) decreases or increases, there is a tendency for the hardness to decrease and increase after storage under high humidity conditions, and there is a range of component (C) content that is optimal for the stability of tablets.
[0242] Based on the results of Examples 2, 5, 6, 14 and 15, it was confirmed that if the total content of component (B) α-starch and component (C) low-substituted hydroxypropyl cellulose or sodium starch glycolate increases, there is a trend of decreasing tablet hardness after storage under high humidity conditions, and there is an optimal range for dissolution and tablet stability.
[0243] The evaluation results of the homogeneity of acotiamide hydrochloride hydrate in the tablets are shown in Figures 2-3 .
[0244] according to Figures 2-3 As a result, in Comparative Examples 2, 8, 11, and 12, there were points where the sulfur content was more than 60%. This indicates that acotiamine hydrochloride hydrate containing sulfur was locally present in the tablet. In contrast, in Examples 2 and 4, there were almost no points where the sulfur content was more than 60%, indicating that acotiamine hydrochloride hydrate was uniformly present in the tablet.
Claims
1. A tablet, characterized in that, Contains a granule comprising (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate, wherein the granule contains more than 65% by mass and less than 91% by mass of component (A) in the unprocessed tablet.
2. The tablet according to claim 1, wherein, The granules are wet granules.
3. The tablet according to claim 1 or 2, wherein, The content of component (B) in the unprocessed tablets is more than 2% by mass and less than 10% by mass.
4. The tablet according to any one of claims 1 to 3, wherein, The content of component (C) in the unprocessed tablets is more than 5% by mass and less than 20% by mass.
5. The tablet according to any one of claims 1 to 4, wherein, The combined content of ingredients (B) and (C) in the raw tablets is 8% by mass or more.
6. The tablet according to any one of claims 1 to 5, wherein, The content of component (B) in the raw tablets is more than 2% by mass and less than 8% by mass.
7. The tablet according to any one of claims 1 to 6, wherein, The content of component (C) in the unprocessed tablets is more than 5% by mass and less than 15% by mass.
8. The tablet according to any one of claims 1 to 7, wherein, The combined content of ingredients (B) and (C) in the unprocessed tablets is 8% by mass or more and 25% by mass or less.
9. The tablet according to any one of claims 1 to 8, wherein, The content of component (B) in the unprocessed tablets is more than 3% by mass and less than 8% by mass.
10. The tablet according to any one of claims 1 to 9, wherein, The combined content of ingredients (B) and (C) in the raw tablets is 8% by mass or more and 22% by mass or less.
11. A method for manufacturing a tablet comprising a step of compressing a wet granule containing (A) acotiamide or a salt thereof, (B) α-starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate, wherein the tablet contains 65% by mass and 91% by mass of component (A) in the unfurled tablet.
12. A tablet comprising a wet-granulated dry powder having a moisture content of 4.0% or more and 11.0% or less, said granulation comprising (D) a pharmaceutically active ingredient, (B) α-substituted starch, and (C) a disintegrant selected from low-substituted hydroxypropyl cellulose and sodium starch glycolate.
13. The tablet according to claim 12, wherein, The moisture content of the wet-granulated dried powder is above 4.0% and below 9.0%.
14. The tablet according to claim 12 or 13, wherein, The tablets have a moisture content of 4.0% or more and 13.0% or less.
15. The tablet according to any one of claims 12 to 14, wherein, The tablets have a moisture content of 4.0% or more and 11.0% or less.
16. The tablet according to any one of claims 12 to 15, wherein, (D) The active ingredient is acotilide or its salt.
17. The tablet according to any one of claims 12 to 16, wherein, The water retention ratio of component (A) and component (B) in the tablet is greater than 0.07 and less than 2.
4.
18. The tablet according to any one of claims 12 to 17, wherein, The water retention ratio of component (A) and component (B) in the tablet is greater than 0.15 and less than 2.0.
Citation Information
Patent Citations
Compressed solid composition
JP1999060476A
Semiconductor storage device
JP2023040926A
Aminothiazole derivatives, drug containing the same and intermediate in the production of the compounds
WO1996036619A1
